(untitled) (JBIOEDRA: Jurnal Pendidikan Biologi, 2024)
Managing learning in the classroom is one of the keys to successful implementation of learning in schools. The busy schedule of students at the Flobamorata Kupang Sports Gifted High School is because it is a school with unique characteristics, making this school have students who are also sports athletes. In this condition, the problems that make learning less effective are physical fatigue, inappropriate strategies, models and approaches, short learning time and the perception that biology learning is especially boring because there are lots of scientific terms. To minimize learning management problems, research needs to be carried out to find solutions to solve existing problems. one of which is implementing fun learning, motivating students through the Card Sort learning strategy which can help students explore knowledge and skills thereby increasing class activities and improving learning outcomes. This research was conducted at the Flobamorata Kupang Sports Gifted High School, Oebobo District, Kupang City in August -December 2018. This research is Classroom Action Research (PTK) which consists of 2 cycles from the results of this research. It was found that there was an increase in students’ biology learning motivation through the application of the Card Sort strategy with the help of torso media on the topic of studying food digestion for class students, which then applied this strategy also had an impact on improving student learning outcomes. The conclusion of this research is, through the application of the Card Sort strategy, learning management can be achieved. , learning outcomes, learning motivation and use of learning media increase.